Ação antibacteriana de nanopartículas de prata em Poli (ácido lático): PLA e estudo da biodegradação - Gibelli, Izabel Cristina (2012)
The biological contamination causes a great depth of concern in the polymers industry, whose materials are used for food packaging. Most of the bacteria are associated to a biofilm; complex microbial ecosystem, well structured; thus, it is essential to search for alternatives which can provide the reduction of biofilm accumulation on the surface. One of the alternatives is the usage of nanomaterial for such control. One example of such material is the silver nanoparticle. The human activities produce a lot of residue which have hard decomposition. Research and production with biodegradable plastic open space to a new market by being driven to ecological awareness. One example of such plastic is Poli (lactic acid) (PLA). The aim of such research was to evaluate the anti-bacterial, biodegradable and inhibitory action in the shaping of biofilms on the modified PLA with silver nanoparticle in concentrations of 0,3, 0,5, 1,0 and 1,5 %. Standard strain Staphylococcus aureus and Escherichia coli were used for the antibacterial activity evaluation, through the Japanese regulation JIS Z 2801:2000. For the biofilm inhibition evaluation, the samples were incubated with biofilm forming strains from S. aureus, E. coli and Pseudomonas aeruginosa in a constant shaking and evaluated in 1, 3 and 7 days. The samples were buried with a humidity air system for observation of natural degradation in organic soil, in favor of its bacterial growing for 328 days. The results show that the silver antibacterial action was around 70% for E. coli and a small inhibition of biofilm was observed on the third day for E. coli and P. aeruginosa. The PLA natural biodegradation was stable for the mass loss as well as he significantly loss of molar mass. The analysis of the compound presented good distribution and bad dispersion, which could have influenced on the antibacterial activity. New process methods for the nanoparticle incorporation must be carried out for better dispersion and availability of PLA silver surface.